Leafhopper subgenus Pedionis (Pedionis) Hamilton, 1980 (Hemiptera: Cicadellidae: Macropsinae) with new species, record, combination and synonymy from Southern China - Li, Hu; Dai, Ren-Huai; Li, Zi-Zhong (Zootaxa, 2017)
A new species Pedionis (Pedionis) damingshanensis sp. nov. from Guangxi of China is described and illustrated, a known species P. (P.) garuda (Distant, 1916) rec. nov. is reported for the first time and redescribed based on 4 specimens in Fujian, Guangdong, Yunnan of China, a new combination P. (P.) hamiltoni (Li, Dai & Li, 2014) comb. nov. from the genus Varicopsella is revealed and a junior synonym Varicopsella (Multispinulosa) Li, Dai & Li, 2014 syn. nov. under Pedionis (Pedionis) Hamilton, 1980 is proposed.